The Impact of Enterprise Management Elements on College Students’ Entrepreneurial Behavior by Complex Adaptive System Theory - Cheng, Yueyuan; Zhang, Junlong; Liu, Yang (Frontiers in Psychology, 2022)
At present, with the continuous rise in public consumption level, the pressure of college students’ entrepreneurship or employment is increasingly severe. Under the concept of positive psychological intervention, the present work aims to alleviate the entrepreneurial pressure of college students and improve college students’ entrepreneurial education and entrepreneurial behavior, through the analysis of enterprise management elements. A three-month intervention experiment including the pre-test, preventive curriculum intervention, post-test, and delayed test is conducted, and a control group and an experimental group are set up, to investigate entrepreneurial intention, emotional management ability, and ability to deal with entrepreneurial pressure of college students. In addition, based on complex adaptive system (CAS), the enterprise management elements are analyzed, and a multi-layer network model is constructed. At the same time, the present work defines the new diversified elements of enterprise management, discusses the effectiveness and psychological impact of diversified management, and proves that psychological security plays an intermediary role in the cross-layer relationship chain in the multi-layer CAS system network. The experimental results indicate that after positive psychological intervention, the pressure of students in the experimental group is generally reduced, the depression and anxiety are also significantly reduced, and all aspects of positive personality have been improved to a certain extent. In addition, in the delayed test after three months, the experimental group can maintain a relatively better state than the control group. By exploring the role effectiveness and characteristics of diversified management, this experiment confirms that the improvement of psychological security under positive psychological intervention has a positive impact on the effectiveness of diversified management. The present work discusses the hierarchical construction in enterprise management, and puts forward reasonable suggestions and theoretical development for the influence of entrepreneurial practice of college students.